Echoes of 2HDM inflation at the collider experiments - Modak, Tanmoy; Oda, Kin-ya (The European physical journal. C, Particles and fields, 2020)
We study the correlation between the constraints on general two Higgs doublet model from Higgs inflation and from collider experiments. The parameter space receives meaningful constraints from direct searches at the large hadron collider and from flavor physics if $$m_H$$, $$m_A$$, and $$m_{H^± }$$are in the sub-TeV range, where H, A, and $$H^± $$are the CP even, CP odd, and charged Higgs bosons, respectively. We find that in the parameter region favored by the Higgs inflation, H, A, and $$H^± $$are nearly degenerate in mass. We show that such near degeneracy can be probed directly in the upcoming runs of the Large Hadron Collider, while the future lepton colliders such as the International Linear Collider and the future circular collider would provide complementary probes.
Gesehen am 09.08.2021